Design, simulation and testing of an array of nano electro mechanical switches (NEMS) - Luay Mahdi; Qais Al-Gayem (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Electro mechanical switches used for multi-purposs applications with ultra small size in nano meter scale, operating in very small voltage in millivolts, approximately zero leakage current due to air gap separation between electrodes with three terminals that easy to control it. Nano electro mechanical switches are electronic switches similar to those used by conventional semiconductor switches in application as they can be used as relays, logic devices. The basic principle of nano electro mechanical switches is electronic switches operation is fundamentally different from semiconductor switches. They have many advantages over conventional semiconductor switches such as low-power digital logic applications, ability to work with very small voltage signals for low dynamic energy consumption, and durability against hostile environments such as high temperatures and radiation contaminated spaces. In this article, we will design, implement, and test a matrix of nano electro mechanical switches by on line test using the superposition theory. The simulations of these switches were implemented using the MATLAB-Simulink and ORCAD Pspice environments. Also, controlling the flow of current was achieved by means of a nanometer movement to make or break the physical contact between the electrodes.